1996
DOI: 10.1002/jbmr.5650111210
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease of bone and quality of life

Abstract: Little is known about how Paget's disease of bone affects quality of life. To better understand the relative impact of factors on quality of life, we mailed a brief survey to 2000 people randomly selected from the Paget's Foundation mailing list. The sample was geographically stratified to examine the effects of specialist availability. Nine hundred and fifty-eight persons responded to the questionnaire (53% response rate after adjustment for death, incorrect addresses, and nondeliverable mailings). The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…(1)(2)(3) Despite the impact of this disease on the population and the health care system, there are only few, mostly isolated hospital-based studies, that address the prevalence of Paget's disease of bone in the United States and the true prevalence of Paget's disease in the United States (or elsewhere) remains unknown.…”
Section: Introduction Pmentioning
confidence: 99%
“…(1)(2)(3) Despite the impact of this disease on the population and the health care system, there are only few, mostly isolated hospital-based studies, that address the prevalence of Paget's disease of bone in the United States and the true prevalence of Paget's disease in the United States (or elsewhere) remains unknown.…”
Section: Introduction Pmentioning
confidence: 99%
“…Other possible complications of PDB can be related to joint involvement inducing secondary osteoarthritis, and nervous system involvement with neurological compression syndromes; in rare cases, a sarcomatous degeneration of Paget bone has been described [1][2][3][4] . The typical signs and symptoms of PDB and its complications may affect the quality of life of the patients, resulting in significant disability 5,6 . Clinical series from hospital referral centers usually involve a high rate of symptomatic patients such as those recognized because of clinical manifestations that lead to the diagnosis, but it is generally accepted that most patients (up to 95%) are asymptomatic and often undiagnosed 7 .…”
mentioning
confidence: 99%
“…(22) Epidemiological studies have quantified fracture risk in cohorts of patients with PDB. (10,(23)(24)(25)(26) Various studies have found a slight to no increase in overall fracture risk (because PDB localizes at one or more skeletal sites, it is important to differentiate between fracture risk at pathological bone sites and overall fracture risk) in patients with PDB. (23,24) However, higher rates of fracture have been reported through pathological bone, even after bisphosphonate treatment.…”
mentioning
confidence: 99%